New Insight on Vitality Differences for the Penaeid Shrimp, Fenneropenaeus chinensis, in Low Salinity Environment Through Transcriptomics - Liu, Jun; Zhang, Daizhen; Zhang, Lei; Wang, Zhengfei; Shen, Jie (Frontiers in Ecology and Evolution, 2022)
In context of global warming, excessive rainfall changes salinity in shrimp farming ponds in a short period and exerts salinity stress on the outdoor breeding shrimp. Previous studies have identified several mechanisms of response to salinity stress in economically important shrimp; however, little is known about the molecular mechanisms of vitality-related metabolic regulation in shrimp living in saline environments. This study based on Fenneropenaeus chinensis using transcriptomics identified 19 differentially expressed genes (DEGs) having the same expression pattern from individuals acclimated in both high and low-salinity environments (low salinity: 10 ppt, isosmotic salinity: 25 ppt) between normal and moribund shrimp. Eight loci were associated with immunity (Pens penaeidins, Crus crustins, ALFs anti-lipopolysaccharide factors, Lac Lachesin, MIH molting-inhibiting hormone-like protein, VAP-A VAMP-associated protein A, SP2 serine protease 2, and CTL C-type lectin protein). Eight were associated with signal transduction (SPTBN1 Spectrin, AASS α-aminoadipic semialdehyde synthase, Moxd1 Monooxygenase DBH-like 1, NAP neuroparsins, VDCCs voltage-dependent calcium channels, CTL-2 Choline transporter-like protein-2, FZD-1 Frizzled-1, and RGS regulator of G-protein signaling 2-like). Others were associated with cell detoxification (ABC Spectron protein, subfamily ABCG), transcriptional regulation (TTK Tramtrack) and antioxidation (SOD1 Cu/Zn superoxide dismutase). For RT-qPCR, the analysis verified the reliability of DEGs in the study by using 12 randomly selected DEGs, including targeted and non-targeted genes. The study indicated the presence of 19 potential genes with important functions independent of the response to salinity stress in modulating the vitality of F. chinensis that could serve as tools in future genetic studies and molecular breeding.